Cameroon : Second Review of the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Second Review of the Three-Year Arrangement Under the Poverty Reduction and Growth Facility for Cameroon. Economic activity is slowing, reflecting a weak business environment, stronger competition from low-cost producers of manufactured products, and reforms to foster sustainable forestry production. Higher world oil prices are leading to inflation pressures while contributing to an improvement in the fiscal position and external current account balance. Budget execution and implementation of structural measures related to public financial management were also satisfactory.